Penerapan Model Pembelajaran Project Based Learning Berbantuan Prototipe Untuk Meningkatkan Keterampilan Praktik Siswa Pada Mata Pelajaran Instalasi Penerangan Listrik Di Smk Negeri 2 Mandau - Daniel Santoso Simanjuntak; Elfizon Elfizon (Journal of Electrical Vocational Education, 2025)
This study aims to identify the effect of implementing the PjBL learning model with the help of a prototype to improve students' practical skills in the subject of electrical lighting installations for class XI TKL at SMK Negeri 2 Mandau. This study integrates learning theory with practical applications through a mini house installation project.The research method used is a quasi-experimental with a one-shot case study design. The research subjects involved 37 students in class XI TKL at SMK Negeri 2 Mandau in the 2024/2025 academic year. This research method has no comparison because there is only one group or one unit of analysis studied. Data were collected after certain events or actions occurred.Based on the results of the research conducted, the average student score increased. The application of the project based learning model assisted by a prototype has been proven to increase students' practical skills scores. This can be seen from the list of student scores before and after the prototype was used. With increasing skills, especially in installation, students are expected to be able to carry out installations at home themselves if needed.